Spatial separation of rotating binary Bose-Einstein condensates by tuning the dipolar interactions - Kumar, Ramavarmaraja Kishor [UNESP]; Tomio, Lauro [UNESP]; Gammal, Arnaldo (Amer Physical Soc, 2019)
We are pointing out relevant anisotropic effects, related to spatial separation and miscibility, due to dipole-dipole interactions in rotating binary dipolar Bose-Einstein condensates by considering symmetric (Dy-164-Dy-162) and asymmetric (Er-168-Dy-164, Dy-164-Rb-87) dipolar mixtures. The binary mixtures are kept in a strong pancake-shaped trap, with repulsive two-body interactions and fixed rotation, modeled by an effective two-dimensional coupled Gross-Pitaevskii equation. The anisotropy of the dipolar interactions on miscibility and vortex-lattice structures is studied by tuning the dipole-dipole interaction (DDI) from repulsive to attractive by varying the dipole polarization angle. A clear spatial separation is verified in the densities for attractive DDI, when the interto intraspecies contact interaction ratio is larger than 1, being angular for symmetric mixtures and radial for asymmetric ones. The signature of hidden vortices is evidenced in the particular dipolar-symmetric case. Another relevant outcome is the observed mass-imbalance sensibility verified by the vortex-pattern binary distributions in symmetric and asymmetric-dipolar mixtures, which requires the use of a relation for nonhomogeneous mixtures to estimate the miscibility of two components.